Modeling and Predicting Heavy-Duty Vehicle Engine-Out and Tailpipe Nitrogen Oxide (NOx) Emissions Using Deep Learning - Pillai, Rinav; Triantopoulos, Vassilis; Berahas, Albert S.; Brusstar, Matthew; Sun, Ruonan; Nevius, Tim; Boehman, André L. (Frontiers in Mechanical Engineering, 2022)
As emissions regulations for transportation become stricter, it is increasingly important to develop accurate nitrogen oxide (NOx) emissions models for heavy-duty vehicles. However, estimation of transient NOx emissions using physics-based models is challenging due to its highly dynamic nature, which arises from the complex interactions between power demand, engine operation, and exhaust aftertreatment efficiency. As an alternative to physics-based models, a multi-dimensional data-driven approach is proposed as a framework to estimate NOx emissions across an extensive set of representative engine and exhaust aftertreatment system operating conditions. This paper employs Deep Neural Networks (DNN) to develop two models, an engine-out NOx and a tailpipe NOx model, to predict heavy-duty vehicle NOx emissions. The DNN models were developed using easily accessible On-board diagnostics (OBD) information from two datasets, an engine dynamometer dataset and a chassis dynamometer dataset. Results from trained DNN models using the engine dynamometer dataset showed that the proposed approach can predict NOx emissions with high accuracy, where R2 scores are higher than 0.99 for both engine-out and tailpipe NOx models on cold/hot Federal Test Procedure (FTP) and Ramped Mode Cycle (RMC) data. Similarly, the engine-out and tailpipe NOx models using the chassis dynamometer dataset achieved R2 scores of 0.97 and 0.93, respectively. All models developed in this study have a mean absolute error percentage of approximately 1% relative to maximum NOx in the datasets, which is comparable to that of physical NOx emissions measurement analyzers. The input feature importance studies conducted in this work validate the development of high accuracy DNN models (R2 = 0.92-0.95) utilizing minimal engine and aftertreatment inputs. This study also demonstrates that DNN NOx emissions models can be very effective tools for fault detection in Selective Catalytic Reduction (SCR) systems.